Synthesis and biological evaluation of novel chiral diazepine derivatives as bombesin receptor subtype-3 (BRS-3) agonists incorporating an antedrug approach. Issue 1 (1st January 2015) - Matsufuji, Tetsuyoshi; Shimada, Kousei; Kobayashi, Shozo; Ichikawa, Masanori; Kawamura, Asuka; Fujimoto, Teppei; Arita, Tsuyoshi; Hara, Takashi; Konishi, Masahiro; Abe-Ohya, Rie; Izumi, Masanori; Sogawa, Yoshitaka; et al.
Graphical abstract